Agronomic Zinc Biofortification of Maize (Zea Mays) and Carrot (Daucus Carota) for Improved Food and Nutrition Security - Prah, Godfred Okyere (University of Cape Coast, 2024)
Micronutrient inadequacies, especially those linked to zinc, pose a significant worldwide public health issue, particularly in low-income nations such as Ghana. Improving the zinc content of primary grains and vegetables that form dietary staples through agricultural biofortification provides an economical solution to combat this problem. The study explored the impact of zinc concentration, timing, and fertilisation method on the yield and uptake efficiency of maize and carrots. The study used a 3-Factoral experiment in a Randomized Complete Block Design with fertilisation rate, stage/time, and method being the experimental factors. The current research in maize demonstrated that zinc concentration had a positive impact on physiological parameters, particularly Fv/Fm ratio, with an increase of over 11 % at a dosage of 6 kg/ha compared to the control. However, the timing and method of applying zinc fertiliser did not directly affect the physiology and growth of maize. Despite the evident link between zinc levels and yield parameters, applying it at 8 kg/ha led to a decreased cob weight, grain weight, and overall maize yield. It is noteworthy that a substantial increase of 52 % in cob weight and 28 % in yield was observed with 6 kg/ha zinc fertilisation relative to the control group. The timing of fertilisation had negligible impacts on most measured physiological and yield parameters in maize; however, there was a notable 15 % increase in cob weight when applied before flowering compared to during grain-filling. Additionally, application of zinc at 8 kg/ha had minimal impact on both physiology and yield traits. Nevertheless, a 26 % increase in grain zinc concentration was observed under 8 kg/ha fertilisation relative to the control. The findings revealed that, foliar zinc fertilisation increased grain zinc concentration of grains by 15.8 % compared to soil application. Also, zinc fertilisation at grain filling improved gain zinc concentration by 16 % compared to pre-anthesis. In carrots, method of application had an insignificant effect on yield and growth. However, there was a progressive increase in yield corresponding to higher zinc fertilisation rates. Typically, a double-fold increase in yield was recorded under 6 kg/ha concentration. Also, a 58 % and 14 % increase in root length and yield were recorded at 30 DAS compared to 50 and 70 DAS. Similarly, root zinc concentration exhibited a positive response with increasing zinc concentration with 30.6 mg/kg and 31.6 µg/g root and shoot zinc concentration recorded at 6 kg/ha level. Application at 30 DAS had a pronounced increase in shoot and root zinc concentration compared to 50 and 70 DAS application time. Hence, it is clear, that zinc agrobiofortification could play a significant role in addressing micronutrient inadequacy however, this is contingent on rate of application and time of application. Although application at 8 kg/ha could be lethal or show diminishing marginal returns regarding growth and yield, however, this significantly increased the concentration of zinc in maize. These findings have profound implications for nutritional security and the fight against hidden hunger, particularly in regions where staple crops are the primary sources of essential micronutrients.
xiv,182p:, ill.
Keywords: Maize Carrots Zinc deficiency Hidden hunger Agronomic biofortification Zinc Fertilisation